Canadian Women Composers in Modernist Terrain: Violet Archer, Jean Coulthard and Barbara Pentland / Des compositrices canadiennes sur le terrain moderne: Violet Archer, Jean Coulthard and Barbara Pentland - Danielson, Janet (Circuit)

(untitled) (Les Presses de l'Université de Montréal, 2009)
AbstractThe successful compositional careers of Jean Coulthard, Barbara Pentland, and Violet Archer spanned all but the first three decades of the twentieth century. Entering a compositional career at this time had many challenges: as Western Canadians, these composers had to establish their credibility with a public that could not be counted on to recognize the worth of their work due to sexist bias and a prevailing critical stance: public approval was evidence of a lack of true creativity. This was especially problematic for women, who had to keep to the center of progressive composition, away from the experimental and conservative margins, in order to gain recognition. Following World War II, the pressure of modernism increased, due at least in part to initiatives by the U. S. Government in occupied Germany, countering the stereotype of the unsophisticated American with a new narrative of American experimental tradition.